Pengaruh Sosialisasi Pajak, Penerapan Pajak UMKM dan Sanksi Perpajakan Terhadap Tingkat Kepatuhan Wajib Pajak: Penelitian - Ellyka Evitasari Purba; Intan Harahap; Afriyani Elizabet Sitorus; Tasya Oren Sagala; Kesia Septina Putri Siagian (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of tax socialization, MSME tax policy implementation, and tax sanctions on the compliance level of MSME taxpayers in Indonesia based on previous research findings. This research employed a literature review method by collecting and examining various academic sources, including journals, books, official reports, and relevant tax regulations. The findings indicate that tax socialization plays an essential role in enhancing taxpayers’ understanding and awareness, although its effectiveness varies depending on the intensity and quality of the delivered information. MSME tax policies—particularly through simplified regulations and lower final tax rates—generally encourage higher compliance, although gaps in understanding remain among small and micro business actors. Meanwhile, tax sanctions consistently appear as the most influential factor affecting compliance, as they create a deterrent effect and increase the perceived risk of violations. Overall, the study emphasizes that taxpayer compliance is shaped by the interaction of educational efforts, regulatory simplicity, and consistent law enforcement. Therefore, strengthening tax socialization, improving accessible and simple policies, and implementing fair and consistent sanctions are essential strategies to enhance MSME taxpayer compliance in Indonesia.